Penghambatan Enzim Alpha-Glukosidase oleh Daun Mimba (Azadirachta indica) dan Rimpang Temu Mangga (Curcuma mangga) - Kusumawati, Nursalinda; Haryoto, Haryoto; Indrayudha, Peni (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
Type 2 diabetes mellitus is a chronic disease of the digestive system characterized by high blood glucose levels. The main enzyme in carbohydrate metabolism is α-glucosidase. One of the therapeutic approaches to treat T2DM is to make glucose uptake into the blood delayed through inhibition of the α-glucosidase enzyme activity. Neem leaves and mango ginger are reported to reduce blood glucose levels. This study aims to determine the potential inhibitor of neem leaves extract and mango ginger extract and their respective fractions on α-glucosidase activity. Simplicia of neem leaves and mango ginger were macerated using 96% ethanol for 24 hours. The ethanol extract of neem leaves and mango rhizome were fractionated using silica gel 60 GF254 as adsorbent and a combination of ethyl acetate and n-hexane as eluent. The extracts of neem leaves and mango rhizome and fractions of both plants were tested for α-glucosidase inhibition with acarbose as a comparison. The results showed that both plants provided inhibitory activity on α-glucosidase with the lowest IC50 value from the semi-polar fraction of neem leaves about 24.16±4.58 μg/mL. Neem leaves and mango ginger have potential as α-glucosidase inhibitors to treat type 2 diabetes mellitus.